Model-Based Evaluation of Maturity Type of Potato Using a Diverse Set of Standard Cultivars and a Segregating Diploid Population - Khan, Muhammad Sohail; van Eck, Herman J.; Struik, Paul C. (Potato research, 2013)
The objective of this paper is to evaluate the performance of the conventional system of classifying maturity type in potato and to provide a concept of maturity type based on crop physiology. We present an approach in which physiological traits are used to quantify and assess maturity type unambiguously for a set of varieties covering a wide range of maturity classes and a diploid F1 population separating for maturity and well-adapted to Dutch growing conditions, both grown in six environments. We defined physiological maturity based on four traits: the duration of maximum green canopy, the area under the green canopy cover progress curve, and the rate and duration of tuber bulking. The results indicated that physiological maturity type criteria tended to define maturity classes less ambiguously than the conventional criterion. Moreover, the conventional criterion was subject to more random noise and lacked stability and/or repeatability compared with the physiological traits. The physiological maturity criteria also illustrated the physiological trade-offs that existed between the selected traits and underlined the subtle complexities in classifying maturity type. This study highlighted the capabilities of different maturity type criteria in discriminating between different maturity classes among the large set of genotypes. Our new approach involving key physiological traits could be beneficial in offering physiology-based criteria to re-define maturity type. An improved criterion based on important physiological traits would allow relating the maturity to crop phenology and physiology. These new criteria may be amenable to further genetic analysis and could help in designing strategies for potato ideotype breeding for genotypes with specific maturity types.